THE ANTI-AUTHORITARIAN ROLE OF DYSTOPIAS: REFLECTIONS ON ERICO VERISSIMO'S NOVEL INCIDENT IN ANTARES - Baptista, Fabiana Maria [UNESP]; Roitberg, Guilherme Prado (Univ Federal Santa Maria, 2019)
The aim of this article is to analyze the relevance of dystopias in the critique to authoritarianism present in the novel Incident in Antares written by Erico Verissimo. After presenting the main characteristics of utopian thought and dystopia as a literary genre, we investigate how Verissimo denounced through his dystopian society the deepest contradictions of a country historically plagued by coups d'etat and military dictatorships. The article also aims to demonstrate how prevailing Verissimo's criticism is, especially regarding to the permanence of authoritarian thought, social inequalities and violations of human rights in Brazil.
Keywords: Erico Verissimo; Incident in Antares; literary dystopias; anti-authoritarianism